Japanese Dative Causative Construction: Synthactical and Semantic Study - Aryani, Made Ratna Dian; Giri, Ni Luh Kade Yuliani (Humanus, 2023)
This research is focused on Japanese causative constructions related to verbs that act datively, both syntactically and semantically. The purpose of this study is to explain the process of forming Japanese causative constructions both syntactically and semantically. The method used in this study is a qualitative descriptive method. This study uses the syntactic theory of Iori’s regarding the formation of causative constructions, Song's theory of the meaning of causative constructions. The data source is taken from the Japanese language corpus, namely http://www.kotonoha.gr.jp/shonagon/. The results of this study indicate that dative verbs can be formed through the process of forming causative constructions in Japanese. The formation process is in the form of a verb that goes through a morphological process [~seru/ ~saseru]. The verb can be either transitive or intransitive. Transitive verbs that act datively, namely, verbs / yomaseta 読ませた '(cause) to read' and intransitive verbs that act datif/ wataraseta 渉らせた '(cause) to cross', and verbs /arukaseta 歩かせた '(cause) to walk '. The intransitive verb is a moving verb '移動/ idoudoushi'.